Reanalyses with and without convergence - (:unkn) unknown (My University, 2021)
The article studies the influences between languages in a plurilingual area, in order to question the concept of convergence. This has the immediate advantage of taking into account the fact that several factors can together create a situation conducive to change by the very fact of their meeting. One of the goals of our contribution is to underline the impact of plurilingualism on the cognitive processing of languages by speakers. Indeed, postcolonial African territories make it possible to observe in real time what speakers do with languages, which is more advantageous than reconstituting situations from past research. The behaviors of multilingual speakers go beyond anything an observer of the language can imagine ex post. By multiplying the resources of their repertoire, plurilingualism multiplies the influx of possibilities of saying and ways of saying and, consequently, the factors of convergence so that a construction is privileged among others. However, there is immense heterogeneity and the practices have little stability (Boutin 2017), to the point that it is impossible to predict what, in the proliferation of syntactic and lexical creations, will remain as a result of code mixtures. Numerous facts about the three languages most commonly in contact in Ivory Coast, French, Jula and Baule, show two levels of convergence: between several factors of sociolinguistic and communicational order, so that an innovation first appears in a single language (Kriegel 2018; Mufwene 2005), and then between languages, when a construction scheme carrying meaning in one or more of these languages has served as a model for reanalysis of shapes in one or more other languages. The notion of reanalysis that I use is close to that of re-functionalization and is easily conceived as a result of unguided acquisition processes. Reanalysis is the result of comprehension strategies, a reinterpretation of the lexicon and the role of morphemes or constructions (Cf. Kriegel 2
Keywords: African Research